Sex-specific association between triglyceride-glucose index and all-cause mortality in patients with osteoporotic fractures: a retrospective cohort study - Guo, Shao-han; Xu, Jian; Gong, Ya-qin; Hu, Wen-bin; Li, Chong; Lu, Ke (Frontiers in Endocrinology, 2025)
BackgroundOsteoporotic fractures (OPFs) pose a considerable global health burden and are linked with an elevated mortality risk. The triglyceride-glucose index (TyG-I) is a recognized marker of insulin resistance across various populations. The association between all-cause mortality (ACM) and the TyG-I has been widely investigated in a variety of clinical settings. The potential sex-specific differences in this association among OPF patients remain uncertain.MethodsIn this retrospective cohort study, 2,307 patients ≥ 50 years old admitted to the hospital between January 2018 and August 2023 for surgical treatment of OPFs were included. The TyG-I was determined using fasting triglyceride and glucose levels measured at admission. The association between ACM and the TyG-I was evaluated by Cox proportional hazards regression, adjusting for possible confounding variables. Analyses were categorized by sex, and subgroup analyses evaluated possible interaction effects. The ACM rates among TyG-I tertiles were compared via Kaplan–Meier curves.ResultsThis research study analyzed 2,307 patients, of whom 247 (10.71%) died from any cause during the follow-up period. In females, a linear association of the TyG-I with ACM was observed even after adjusting for confounders, with each unit increase in the TyG-I correlating with a 37% increased risk of death (HR: 1.37, 95% CI: 1.06-1.77, p = 0.02). However, in males, there was a non-linear correlation, where patients in the uppermost TyG-I tertile showed a substantially decreased mortality risk relative to those in the lowest tertile (HR: 0.53, 95% CI: 0.30–0.92, p = 0.02). TyG-I indicated a statistically significant relation with sex (P for interaction = 0.01).ConclusionIn patients diagnosed with OPFs, distinct sex-specific variations were observed in the relationship between ACM and the TyG-I. Among female patients, each unit increase in the TyG-I was linked to a 37% greater risk of mortality. Conversely, male patients within the highest TyG-I tertile indicated a lower mortality risk than those in the lowest tertile. Further research is required to confirm these sex-specific associations.